Assessing the impact of a rare synonymous variant in the KNG1 gene on the development of hereditary angioedema - N. A. Pechnikova; Yu. V. Ostankova; M. A. Saitgalina; A. M. Bebyakov; A. A. Totolian (Медицинская иммунология, 2024)
The main cause of edema in hereditary angioedema (HAE) is due to elevated bradykinin levels, caused either by C1-INH deficiency/change in functional activity and caused by mutations in the SERPING1 gene or by mutations in the F12, PLG, ANGPT1, KNG1, MYOF and HS3ST6 genes with a normal level and functionality of the C1-esterase inhibitor. The aim of the work was in silico prognostic analysis of the rare synonymous variant NC_000003.12:g.186725098T>C in the KNG1 gene and its impact on the development of HAE symptoms. The material was a whole blood sample obtained from a woman with clinical manifestations of hereditary angioedema without a decrease in the levels and function of the C1 inhibitor. The research methods included whole exome sequencing, bioinformatic analysis of the KNG1 gene mutation using a number of databases and web resources. Results. When processing full-exome sequencing data, we detected a synonymous variant in the KNG1 gene (exon 4, isoform 1): NC_000003.12:g.186725098T>C. The patient is a heterozygous carrier of the variant, with a frequency of 0.000004 (1:264690). Presumably, the identified variant can lead to the development of sporadic edema through several pathways that are associated with the formation of bradykinin or its analogues. Therefore, (1) the mutant high-molecular-weight kininogen is more easily activated by kallikrein and becomes a source of bradykinin formation through the kallikrein-kinin system; (2) the mechanism of bradykinin formation undergoes significant changes and results in the formation of functionally active but aberrant bradykinin, which alters its inactivation by enzymes with a consequent increase in its half-life, (3) the changes in positions 380-389 bring about modifications in Lys-bradykinin reproduction such that in subsequent steps it is “easily” cleaved to bradykinin by arginine aminopeptidase. The results of our study therefore indicate a possible role of the identified variant in the KNG1 gene in the development of HAE.